Analisis Potensial Kejadian Luar Biasa DBD Berdasarkan Kasus DBD 5 Tahun Terakhir 2019-2024 : Studi Ekologi di Kota Lubuklinggau Provinsi Sumatera Selatan - Anggraini, Sely; Wahyono, Tri Yunis Miko; Fitria, Fitria; Putri, Nadia (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia, with a high potential for outbreaks, particularly in tropical and densely populated regions such as Lubuklinggau City. This study aimed to assess the outbreak potential of DHF in Lubuklinggau by analyzing the five-year trend of minimum and maximum case numbers (2019–2023) and comparing them with 2024 data using the epidemic threshold approach. A descriptive ecological study design was employed, with all primary health centers (puskesmas) in the city as units of analysis. Data sources included annual DHF surveillance reports from the District Health Office, field observations, demographic data from the Central Bureau of Statistics (BPS), and rainfall distribution maps from the South Sumatra Meteorological Agency (BMKG). The findings revealed a significant increase in DHF cases in 2024, with a total of 284 cases and a monthly average of 23.67, exceeding the epidemic threshold of 16.85. Outbreak conditions were identified in six months: April, May, July, August, November, and December. Exceptionally high rainfall in November 2024 is suspected to have contributed to the spike in cases observed in December. The highest number of cases occurred in the service area of the Citra Medika Health Center, which has the second-highest population density in the city. The main risk factors identified included inadequate mosquito breeding site control (PSN) practices and limited laboratory diagnostic capacity. These results underscore the need to strengthen active surveillance at the primary healthcare level, implement widespread public education on the 3M Plus strategy, enhance community participation in larval monitoring and vector control activities, and improve laboratory capacity to support early diagnosis and effective outbreak response. Keywords : Dengue Hemorrhagic Fever, Outbreak, Surveillance, Lubuklinggau, Ecological Study